Does productivity of Islamic banks endure progress or regress?: Empirical evidence using data envelopment analysis based Malmquist Productivity Index - Kamarudin F.; Hue C.Z.; Sufian F.; Mohamad Anwar N.A. (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/SCOPUS